DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWANDI UPTD PPV-DINAS PERTANIAN PROVINSI BANTEN (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This study aims to analyze the influence of work discipline and job satisfaction on employee performance at the Regional Technical Implementation Unit (UPTD) for Veterinary Services and Testing (PPV) of the Banten Provincial Agriculture Office. This study was conducted to understand the dynamics of organizations in the public sector, which often face challenges in maintaining productivity and service efficiency. Data on employee work discipline was collected through attendance records for the period January–December 2024, which included indicators such as tardiness, early departure, and unexcused absences. Meanwhile, job satisfaction was measured through a theoretical questionnaire based on Herzberg's model, which evaluates motivational aspects (such as recognition and self-development) and hygienic aspects (such as salary and work environment). The approach used was explanatory quantitative with a total population of 10 active employees, allowing for a comprehensive analysis without random sampling.The analysis results indicate a significant joint effect between work discipline and job satisfaction on employee performance, with an estimated effect ranging from 0.36 to 6.32 days. Employees with high discipline tend to show better performance, while high job satisfaction strengthens this relationship, producing a synergistic effect. These findings align with previous research by Ariansyah et al. (2025), Riwiyati et al. (2025), and Suharti & Prasetia (2025), which confirm that discipline and job satisfaction contribute to the productivity of public sector employees. Additionally, Kopong & Untajana (2025) and Claudia et al. (2025) also support the notion that high job satisfaction can mitigate the negative effects of low discipline.This study recommends the need for a digital-based attendance monitoring system to improve discipline, as well as improvements in the work environment and development opportunities to foster job satisfaction. This combination of strategies can enhance employee performance and support the efficiency of veterinary services at the UPTD PPV, providing long-term benefits for the public sector in the region.